Sperm Longevity and Motility in Ringer’s Lactate Solution with Addition of Egg Yolk among Five Phenotypes of Kokok Balenggek Chicken - Ananda Ananda; Jaswandi Jaswandi; Rusfidra Rusfidra; Harif Gusdinal (Faculty of Animal Science, Universitas Gadjah Mada, 2023)
The application of cryopreservation to preserve germplasm in such specific breed requires preliminary studies, primarily related to the resistance of spermatozoa to low temperatures (4 – 5 °C) as measured by their motility and longevity. In this study, semen taken from five phenotypes of Kokok Balengeek Chicken (KBC) (Biriang, Jalak, Kinantan, Kuriak, and Taduang) was used to evaluate the effect of Ringer’s Lactate-egg yolk diluent on longevity and motility of spermatozoa. The treatments consisted of Ringer’s Lactate (RL) solution added with egg yolk at a concentration of 1% (RLKT1), 3% (RLKT3), and 5% (RLKT5). Evaluation of fresh semen showed that the spermatozoa of Jalak had the highest motility, namely 75.63 ± 0.5% (P<0.05). Post-dilution longevity and motility observations were carried out at 0, 24, 48, and 72 h, significantly decreasing each time (P<0.05). The lowest range of reduction was found in Jalak spermatozoa diluted with RL with longevity of 7.75 ± 0.70 days. Overall, the RL diluent showed the highest motility after 24 h, namely 41.13 ± 2.27%. Adding egg yolks to Ringer's Lactate solution could not maintain the motility of KBC spermatozoa when stored at 4-5°C for 48-72 h.